Contemporary Existance and Relevance of the Law of Use of Force, the United Nations and the UN Charter - Afriansyah, Arie (UI Scholars Hub, 2007)
The increasing number of the breaking of international law especially the use of military force by the States, the regulation in military violence in international relations is not relevant anymore. Even the United Nations and the provision in the Charter considered can not face the reality in the world right now. But, that opinion can not be justified because many of the states in the world always trying to find the justification in international law for all of the action by the states.